Transaksi Properti Perumahan di Wilayah Perkotaan Indonesia: 2003 -2010 - , Arridel Mindra, S.Pi.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Transactions occur as a result of interaction between the two groups of market participants, the potential buyers (non-owners) on the demand side, and potential sellers (owners) on the supply side. Behavior of residential property transactions differ between regions both nationally, regionally and in the world. Transaction behavioral for housing property has some differences between regions both nationally, regionally and in the world. This study aims to understand the general transaction for housing properties as well as the factors that influence. Transaction for housing properties are also reviewed based on class market segment of small, medium and large. Governmentâs policyies have also seen the impact on transaction for housing property. The reserch was conducted in 10 major city in Indonesia based on housing property survey data conducted by Bank Indonesia and BPS for 8 years (2003- 2010). Transaction for housing properties as well as the factors that influence were analyzed through regression analysis of panel data, while interest rate policy analysis through simulation analysis. Generally, this research found that interest rates and income is elastic to housing properties transaction in the long term, speculative factor is inelastic in the long term and short term. Interest rates and income more elastic to transaction for smaller housing types, followed by middle type and large type. Market speculation factor more elastic to transaction for large housing types, followed by smaller type and middle type. The influence of the type of speculation on house purchases indicate a tendency not to live alone (use value) but for rent or sale at a later time (transfer value). The monetary instruments by interest rate policy to control the transaction for housing through interest rate subsidies or down payment subsidies to encourage home ownership for people, especially for the lower middle class.